Altmetric and Bibliometric Scores: Does Open Access Matter? - Poplašen, Lovela Machala; Grgić, Ivana Hebrang (Qualitative and Quantitative Methods in Libraries; Vol 5 No 2 (2016): June 2016 Issue, 2017)
Since new publishing models and new communication channels are being developed, traditional ways of measuring journal and article impact are not sufficient – besides bibliometrics, altmetrics arises as a new method based on quantitative analysis of mentions on blogs, in the news, shares on social networking sites etc. The main purpose of the study is to analyze the altmetric indicators for Altmetric top 100 articles in 2014, and to compare them with traditional bibliometric data for the same articles. Also, altmetric scores for Open Access (OA) articles are compared to the scores for non-OA articles. The research confirms low correlation between the number of citations (in the first year after publication) and the altmetric score. Nevertheless, the altmetric score has a potential role in promoting articles and getting post-publication evaluation and feedback.